Studi Evaluasi Ekonomi dan Pandangan Masyarakat Terhadap Wisata Pantai Holtekam di Jayapura - Marsi Adi Purwadi; Bernadetha Lumban Gaol (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2024)
This study aims to analyze the economic valuation and perception of the Holtekam Beach tourist attraction in Jayapura City. Questionnaires and interviews were used to collect information on visitor perceptions and satisfaction with Holtekam Beach. This data included assessments of beach facilities (toilets, trash cans, seating, etc.), local community attitudes, and visitors' general assessments of the beach's comfort and attractiveness. The primary approach used was linear regression analysis, which allowed researchers to identify the relationship between the dependent variable (frequency of visits) and the independent variable (cost of a single visit). The analysis showed that Holtekam Beach has significant economic value, calculated using the consumer surplus method based on tourist expenditure. The average consumer surplus value per individual was Rp. 48,820, indicating the value perceived by Holtekam Beach visitors as an additional benefit to the cost of visiting the beach. This reflects the benefits or satisfaction gained by visitors beyond the costs incurred. This value also indicates that, despite the costs incurred, visitors are still satisfied with their visit. Assuming an average of 125,000 tourists visit Holtekam Beach annually, the total economic value generated by Holtekam Beach tourism is IDR 6,102,573,762.69. Visitors generally have a positive perception of Holtekam Beach's natural beauty, particularly its panoramic views and cleanliness. However, some facilities, such as souvenir shops and rental services, are still considered inadequate by visitors, which impacts their level of satisfaction. Factors such as cleanliness, safety, and comfort of facilities influence overall visitor satisfaction. Key Words : Economic Valuation, Perception, Tourist Attraction